KARAKTERISASI MORFOLOGI DAN AGRONOMI LIMA AKSESI TOMAT (Solanum lycopersicum L.) LOKAL KUTOARJO - Dani Arya Armadhan; Elea Nur Aziza; Annisa Khoiriyah (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2026)
This study aimed to characterize the morphological and agronomic traits of five local tomato accessions from Kutoarjo (A, B, C, D, and E) as a foundation for plant breeding programs. The experiment was conducted using a randomized complete block design with six replications. Observations included qualitative and quantitative characters based on the IPGRI and UPOV descriptor guidelines. The analysis results proved that vegetative traits, such as plant height, stem diameter, and leaf size, did not show significant differences among the accessions. In contrast, generative traits (days to flowering, fruit size, productivity, and seed weight) showed highly significant differences. The Kutoarjo E accession exhibited the best agronomic performance with a productivity of 2.20 kg/plant, 67.83 fruits/plant, and a 1000-seed weight of 3.47 g. In conclusion, these local tomato accessions possess phenotypic and agronomic variations with great potential for sustainable utilization as basic breeding materials.